Perbandingan Indeks Massa Tubuh Pada Pasien Hipertensi Dengan Tekanan Darah Yang Terkontrol dan Tidak Terkontrol di RSUD Arifin Achmad Provinsi Riau - Eka Bebasari; Dimas Pramita Nugraha (Jurnal Ilmu Kedokteran, 2017)
The nutritional status is a factor that related with blood pressure. The nutritional status that indicated by body massindex (BMI) needs to be considered in management of hypertension. This study was a cross-sectional analytic thatassess relationship between BMI and hypertension controlled. The subjects of the study were hypertension patientsthat visit outpatient clinic of Arifin Ahmad General Hospital, Riau Province. Datas were analyzed by unpaired t-test.The results showed that patients with obesity grade 1 were more frequent in controlled hypertension group comparedto uncontrolled hypertension (43.8% vs 32.5%). The BMI average in patients with controlled hypertension group was24.2, while in uncontrolled hypertension group was 24.8 (p>0.05). There was no statistically significant differencebetween BMI in both groups patients.